2020
DOI: 10.1007/s43452-020-00120-3
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the in situ testing of the moisture content of brick walls: an example of application

Abstract: The article presents original methodology of testing the moisture content of brick walls in buildings. It was developed on the basis of own experience acquired during testing the moisture content in many excessively wet buildings erected in various historical periods. The tests were conducted using different methods, including non-destructive methods. To emphasize the importance of the problem, an overview of the methodology was preceded by a brief presentation of the causes and negative effects of excessive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 16 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Test results, obtained through use ofmercury intrusion porosimetry, are given in Table 6 and shown in Figures 7 and 8. The study shows that the samples extracted from masonry units operated for 35 years in outdoor environmental conditions have a total porosity value of 33.35% and a bulk density of 1.668 g/cm 3 . Group B samples stored in laboratory conditions have a similar total porosity value of 33.25% and a bulk density of 1.680 g/cm 3 to group A samples.…”
Section: Porositymentioning
confidence: 96%
See 1 more Smart Citation
“…Test results, obtained through use ofmercury intrusion porosimetry, are given in Table 6 and shown in Figures 7 and 8. The study shows that the samples extracted from masonry units operated for 35 years in outdoor environmental conditions have a total porosity value of 33.35% and a bulk density of 1.668 g/cm 3 . Group B samples stored in laboratory conditions have a similar total porosity value of 33.25% and a bulk density of 1.680 g/cm 3 to group A samples.…”
Section: Porositymentioning
confidence: 96%
“…It is important that these walls are protected against capillary rising water from the ground and do not show moisture damage typically caused by water in combination with soluble salts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Holownia [9] showed that linear bridges are responsible for about 20% of the total heat losses through the external wall. In areas where thermal bridges occur, in addition to the increase in heat flow, there is a decrease in temperature, which may cause surface 2 of 16 condensation and mould appearance [10]. Ujma and Kysiak [11] indicated that, apart from deterioration in user comfort (e.g., lower room temperature, occurrence of air drafts), thermal bridges also contribute to crack formation on the building facade.…”
Section: Introductionmentioning
confidence: 99%
“…A significant concern is the presence of moisture inside brick walls, which can have serious consequences for the health of people who live in these structures and the maintenance and dependability of the buildings in question [1,2]. Monuments and medieval and historical structures are particularly vulnerable to moisture damage [3]. In order to protect the foundations of buildings built more than a century ago from soil moisture, simple procedures were used.…”
Section: Introductionmentioning
confidence: 99%